Analysis Of Impacts Affecting Company Value with Dividend Policy as A Moderating Variable on Manufacturing Companies Listed on The Indonesia Stock Exchange for the 2016-2018 Period - Alexander Virgiawan Liany Oleona (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The main purpose of this study is to test the debt and profitability policy variables that affect firm value by adding a moderating variable, namely dividend policy in manufacturing companies listed-on the IDX from 2016 to-2018. 17 companies were used as samples in this study using purposive sampling method. This study uses various research techniques such as descriptive statistics, classical hypothesis testing, multiple linear regression analysis and there is also moderate regression analysis (MRA) and processing results using IBM SPSS version 25. Briefly in the partial test (t) debt policy has a positive value but does not significantly affect firm value, and profitability has a negative value but significantly affects firm value. As for the moderating variable, dividend policy does not strengthen the relationship or is unable to moderate the relationship between debt policy and firm value and for the second test of moderation, dividend policy is able to strengthen the relationship between profitability and firm value.